Exploring the Meaning of Easter in the Context of Moderate Religious Life for BP PAR and BP. PAM Congregation of GKI Hermon Hollo Him - Banga, Berthin S; Roragabar, Yeni I; Hutapea, Melina; Irianto, Irianto; Lesirolo, Tresia; Erlangga, Dina Surya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The challenge of understanding the meaning of Easter in the context of moderate religious life is significant in accommodating the plurality of beliefs. Easter symbolizes transformation, forgiveness, and hope for humanity. Understanding these symbols can be a meeting point between various religious beliefs in a moderate religious life. Through important activities such as PkM in helping teenagers (BP. PAR) and Christian youth (BP. PAM) at the GKI Hermon Hollo Him congregation integrate Easter values in daily life and become witnesses of Christ in society. Activities are carried out using lectures, discussions, and question-and-answer methods. Through PkM, BP. PAR and BP. PAM GKI Hermon Hollo Him managed to deepen their understanding of the meaning of Easter, broaden their horizons about moderate religious life, and strengthen the concept of inclusiveness in the congregation. This improves relationships with God and others and enriches their contribution to society with the values of love, tolerance, and inclusiveness.